Energy and Exergy Analysis on a Blast Furnace Gas-Driven Cascade Power Cycle - Hao Chen; Yiming Wang; Linbo Yan; Ziliang Wang; Boshu He; Baizeng Fang (Energies, 2022)
Blast furnace gas is the major combustible by-product produced in the steel industry, where iron ore is reduced by coke into iron. Direct combustion of blast furnace gas after simple treatment for power generation is a common utilization method nowadays. However, this method suffers from low efficiency and high carbon intensity. The use of gas-steam combined cycle is an excellent method to improve the efficiency of blast furnace gas for power generation. However, there is a problem of insufficient utilization of low product heat, and the addition of CCS system can further reduce the power efficiency. To solve these issues, a new blast furnace gas power generation system with a Brayton cycle with supercritical CO2 and a Rankine cycle with transcritical CO2 is proposed in this work. The new system is then thermodynamically simulated by Aspen Plus, after the sub-modules are validated. The effects of molar ratio of steam to carbon, selexol/CO2 mass ratio, compression ratio, turbine import temperature and turbine inlet pressure on the system are investigated. A comparison is also performed between the new combined cycle system and the traditional combined cycle power generation system. The results show that in the new power generation system, net power efficiency of 53.29%, carbon capture efficiency of 95.78% and sulfur capture rate of 94.46% can be achieved, which is significantly better than the performance of the conventional combined cycle.